TINGKAT UMUR DAN PARITAS IBU HAMIL DENGAN KEJADIAN PRE-EKLAMPSIA - Rachel Dwi Wilujeng (Jurnal Kebidanan Akademi Kebidanan Griya Husada Surabaya, 2018)
Pre-eclampsia is a disease with signs of hypertension, edema and proteinuri that arise due to pregnancy that occurs in the third quarter (Hanifa, 2002). In the last 3 years the incidence of pre-eclampsia in Brawijaya Hospital Surabaya in 2014 - 2015 has increased by 0.84% ??and an increase from 2015 - 2016 of 1.12%. The pre-eclampsia event in 2017 described the incidence of pre-eclampsia in pregnant women based on age and parity in the period January-June 2017 and the tolerance rate according to the East Java Health Office at 5% could have an impact on prematurity until the death of the fetus in the womb, whereas in mothers there is inpending eclampsia up to eclampsia, and it can be a death in the mother. Factors that can increase the incidence of pre-eclampsia, ie at the age of <20 years and> 35 years, tend to experience pre-eclampsia and in multigravida pre-eclampsia can occur because the mother's uterus was initially empty without a fetus and pregnancy. Method: The study used the descriptive method of the study population were all pregnant women who examined in January - June 2017 as many as 530 people. The study sample consisted of 86 research people using systematic random sampling. Results: The results of the study showed that the incidence of pre-eclampsia was 15 people (17.44%), the majority of pregnant women> 35 were 12 people (27.27%) with a total of 6 people (27.27%). At the age of the majority of occurrences of pregnant women who experience pre-eclampsia occur at the age of ? 35 years as many as 12 people (27.27%). Whereas in the parity it was found that the majority of the cases of pregnant women who had pre-eclampsia occurred in the community as many as 6 people (27.27%). Discussion: It can be concluded that the incidence of pre-eclampsia is influenced by age and parity. Therefore, to reduce the incidence of pre-eclampsia early and routine examination is needed in pregnancy, so that complications can be detected early and immediately treat it, regulate food diets and expect pregnancies at reproductive age (20-35 years) so that pre-eclampsia in mothers getting pregnant can be handled quickly and precisely.